High Sensitivity Troponin T as Complementary Modality for Determining Doxorubicin Regimen Cardiotoxicity in Non-Hodgkin Lymphoma Patients - Ami Ashariati Prayogo; Satriyo Dwi Suryantoro; Merlyna Savitri; Winona May Hendrata; Andi Yasmin Wijaya; Budi Susetyo Pikir (Advanced Pharmaceutical Bulletin, 2022)
Purpose: This study aims to evaluate the role of high-sensitivity troponin T (hsTnT) as a complementary tool for determining cardiotoxicity in non-Hodgkin lymphoma (NHL) patients receiving cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) regimen chemotherapy. Methods: We included 35 patients diagnosed with NHL who received CHOP chemotherapy. Left ventricular ejection fraction (LVEF) and hsTnT were measured at two time points: before the first cycle (pre-test) and after the fourth cycle (post-test). The LVEF and hsTnT were analysed using IBM SPSS version 24 through the paired-sample T-test, Wilcoxon signed-rank test, Pearson’s correlation and Spearman’s correlation. Results: There was a significant difference in both LVEF and hsTnT between pre-chemotherapy and post-4th chemotherapy cycles (p = 0.001). However, more contrast difference from the baseline value of hsTnT compared to LVEF could be observed. LVEF did not detect any deterioration in myocardial function. However, 10 out of 35 subjects exhibit hsTnT higher than the 99th percentile of the population (>14 pg/ml), suggesting that myocardial injury (MI) could be detected. There was no correlation between LVEF and hsTnT (p > 0.05). Conclusion: HsTnT, together with LVEF, could complement each other and offer better coverage for detecting cardiotoxicity during the administration of CHOP in NHL patients. An insignificant correlation between hsTnT and LVEF showed that cardiotoxicity existed in a broad spectrum including cellular damage and functional impairment, as hsTnT represents cellular damage, and LVEF reflects heart functional capacity.